Accounting and Taxation of the Performance of Entities Under Ias 12 'Corporate Income Tax' - Application Particularities - Danescu, Magdalena; Soare, Janina (Acta Universitatis Danubius. Œconomica, 2023)
Calculating and accounting only for current tax is not sufficient if, due to accounting policies or legal provisions, the tax value of assets and liabilities is different from their book value. Profits or losses are shown in the profit and loss account, while some gains or losses (other than those shown in the profit and loss account) are shown in reserves or retained earnings. To the extent that the taxation of certain profits or the deduction of certain tax losses is deferred to future periods, as well as in situations where some amounts shown in the reserve accounts or retained earnings are to be taxed in the future as a result of provisions in tax legislation, a deferred income tax liability must be recognized in the accounts. The transition to IFRS has led to the recognition of deferred taxes, receivable or payable, depending on the situation of each entity, in the profit and loss account, the retained earnings account or the reserve accounts.